Influencia del Sistema de Gestión de Seguridad y Salud en el Trabajo (Ley N° 29783) en el incremento de la productividad en la Empresa Star Print S.A. - Carrera Abanto, Yober (2022)
The objective was to Determine the Influence of the Occupational Health and Safety Management System (SGSST) (Law 29783) in the Increase in Productivity of the Estar Print company, it was possible to appreciate at the beginning that the conditions of the SGSST did not reach the compliance of the Estar Print Company, in addition to the productivity indices were not favorable either, the study has shown that the correct implementation of an SGSST is favorable to improve productivity, it also improves the work environment, since by going to ensure the conditions of work, there is a favorable environment for work. The process has considered induction, implementation and training that strengthened capacities, attitudes, skills, knowledge, and values, generating a culture of prevention, safety, and occupational health. The investigation has established as favorable that the SGSST favors safety and all the processes of a safe environment or work environment that facilitated a culture of prevention, safety, for the sake of productivity.